PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF ACTIVATING STUDENTS’ LEARNING AND COGNITIVE MOTIVATION IN UZBEK LITERATURE EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the pedagogical and psychological features of activating students’ learning and cognitive motivation in Uzbek literature education. In modern pedagogical practice, the teaching of literature is not limited to transmitting information about writers, literary periods, genres, and artistic texts; it also requires the formation of students’ intellectual curiosity, aesthetic perception, independent thinking, emotional responsiveness, and value-based attitude toward national literary heritage. The study emphasizes that learning and cognitive motivation in Uzbek literature classes develops through the interaction of pedagogical conditions, psychological needs, methodological approaches, and the meaningful organization of literary analysis. Special attention is given to the role of problem-based learning, dialogic communication, interpretive reading, creative assignments, and student-centered methods in increasing learners’ active participation. The article argues that motivation becomes more stable when literary education connects artistic texts with students’ personal experience, moral reflection, cultural identity, and professional development. The findings may be useful for improving the methodology of Uzbek literature education in pedagogical universities.